Isavuconazole Is as Effective as and Better Tolerated Than Voriconazole for Antifungal Prophylaxis in Lung Transplant Recipients. (28th May 2020) - Samanta, Palash; Clancy, Cornelius J; Marini, Rachel V; Rivosecchi, Ryan M; McCreary, Erin K; Shields, Ryan K; Falcione, Bonnie A; Viehman, Alex; Sacha, Lauren; Kwak, Eun Jeong; Silveira, Fernanda P; Sanchez, Pablo G; et al.
Abstract: Background: Invasive fungal infections (IFIs) are common following lung transplantation. Isavuconazole is unstudied as prophylaxis in organ transplant recipients. We compared effectiveness and tolerability of isavuconazole and voriconazole prophylaxis in lung transplant recipients. Methods: A single-center, retrospective study of patients who received isavuconazole (September 2015–February 2018) or voriconazole (September 2013–September 2015) for antifungal prophylaxis. IFIs were defined by EORTC/MSG criteria. Results: Patients received isavuconazole (n = 144) or voriconazole (n = 156) for median 3.4 and 3.1 months, respectively. Adjunctive inhaled amphotericin B (iAmB) was administered to 100% and 41% of patients in the respective groups. At 1 year, 8% of patients receiving isavuconazole or voriconazole developed IFIs. For both groups, 70% and 30% of IFIs were caused by molds and yeasts, respectively, and breakthrough IFI (bIFI) rate was 3%. Outcomes did not significantly differ for patients receiving or not receiving iAmB. Independent risk factors for bIFI and breakthrough invasive mold infection (bIMI) were mold-positive respiratory culture and red blood cell transfusion >7 units at transplant. Bronchial necrosis >2 cm from anastomosis and basiliximab induction were also independent risk factors for bIMI. Isavuconazole and voriconazole were discontinued prematurely due to adverse events in 11% and 36% of patients, respectively ( P  = .0001). Most common causes of voriconazole and isavuconazole discontinuation were hepatotoxicity and lack of oral intake, respectively. Patients receiving ≥90 days prophylaxis had fewer IFIs at 1 year (3% vs 9%, P  = .02). IFIs were associated with increased mortality ( P  = .0001) and longer hospitalizations ( P  = .0005). Conclusions: Isavuconazole was effective and well tolerated as antifungal prophylaxis following lung transplantation. Abstract : Isavuconazole was as effective as and better tolerated than voriconazole in preventing invasive fungal infections (IFIs) after lung transplantation. Breakthrough IFIs occurred in 3% of patients receiving isavuconazole or voriconazole prophylaxis. IFIs were associated with increased mortality and longer hospitalizations.